Rancang Bangun Mesin Pencacah Rumput Dan Pelepah Kelapa Sawit Dengan Penggerak Motor Bensin Sebagai Pakan Ternak - Hasbi Assiddiq S (Infotekmesin, 2022)
In increasing the productivity of cattle using the cage method, adequate feed availability is needed. In the process of providing feed, farmers in Mandala Village still use the traditional method of chopping feed which requires a lot of energy and time. The purpose of this study was to make a chopping machine for animal feed and to find out the results of the machine chopping. The methods used are observation, literature review, and experimental methods. The grass chopper machine as a result of the research has a chopping chamber size of 36 x 36 x 49 cm, blade 27 x 5 x 1 cm, with a gasoline motor drive of 5.5 HP, transmission pulley and V-belt type A-45. The results obtained were 5 kg of grass using 02.07 minutes, 19.25 kg of trees and banana leaves in 02.48 minutes, while for midrib and palm leaves of 5.75 kg it took 02.25 minutes with each size of the chopped results between 3 -6 cm at engine speed between 2000-2260 rpm.